Comparative Microbial Ecology of Fresh Water and Brackish Water Prawn Farms - P.K., Surendran; Thampuran, Nirmala; V., Narayanan Nambiar (Fishery Technology, 2025)
Microbiological characteristics of fresh and brackish water prawn farms along with their physico-chemical parameters have been investigated. Even though water quality was within the accepted limits in the two farms, there were appreciable variations between the two in respect of pH and dissolved oxygen. Total bacterial counts of the water, mud and the cultured prawn from fresh water farm registered lower values, compared with those from the brackish water farm. However indicator bacteria like total coliforms and faecal coliforms were high in number in the fresh water farm. Human pathogenic bacteria like Salmonella, Enteropathogenic Â£. coli 0157:H7, Listeria menocytogenes, Vibrio chderae, Aeromonas, Enterotoxigenic Bacillus cemts, Plessiomonas shigdloides and other pathogenic Vibrios were also monitored in respect of two types of farm environments. Antibiotic resistance pattern of the bacterial cultures from the two farms towards seven commonly used antibiotics showed comparable values.